Pendampingan WALHI Terhadap Kelompok Perempuan Beremis dalam Menolak Tambang Pasir Besi di Desa Pasar Seluma - Bella Febriyanti; Hajar Gelis Pramudyasmono; Ika Pasca Himawati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This research is motivated by social and ecological conflicts resulting from the planned iron sand mining by PT Faminglevto Bakti Abadi (FBA) in Pasar Seluma Village, Bengkulu, which threatens the coastal ecosystem and the livelihoods of the community, particularly the women's mussel collectors. This study aims to analyze the assistance provided by the Indonesian Forum for the Environment (WALHI) Bengkulu to the Women's Group of Mussel Collectors in rejecting iron sand mining activities. This study uses qualitative methods with data collection techniques through non-participant observation, in-depth interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. Based on conflict theory and a structural functional perspective, WALHI Bengkulu's assistance is understood as a form of social resistance against the dominance of capital interests as well as a mechanism for strengthening the role and collective solidarity of coastal communities. The results show that WALHI Bengkulu's assistance plays an important role in strengthening the critical awareness, organizational capacity, and bargaining power of the women's group of mussel collectors. Forms of assistance include environmental education, legal advocacy, public campaigns, demonstrations, audiences with the government, and alternative economic development. This study concludes that WALHI Bengkulu's assistance contributed significantly to strengthening the collective resistance of coastal women as well as efforts to protect coastal ecosystems and achieve social and environmental justice in Pasar Seluma Village.